Meningkatkan Minat Baca Siswa Melalui Metode Reading Challenge - Supiatman, Lis; Maulidiah, Rina Hayati (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
This activity aims to overcome a problem regarding students' interest in reading at UPTD State Elementary School 014672 Tanjung Alam which is considered still low. This can be identified through the results of the 2022 education report card and also from observations regarding the implementation of the School Literacy Movement (GLS). It is hoped that the literacy movement that has been implemented in schools can help students improve their literacy skills. However, on the contrary, this movement has not been carried out optimally so that literacy skills are still low. Students' literacy skills are low because students' interest in reading is also low. Therefore, teachers in this case should have creativity in accompanying the implementation of school literacy movement activities. One way to increase students' reading comprehension is by implementing a reading challenge method. In this method, students will be invited to go to the reading corner or library to read books they like. The teacher here supervises or monitors students who are reading. Then, 15 minutes before the lesson starts, students report to the teacher the books they have read. For students who read the most, for example in one month, that student is given a reward. Through this activity, it is hoped that students at the school will be able to increase their interest in reading. Keywords: reading challenge method; reading interest; school literacy movement.